Freedom Restrictive Coercive Measures in Forensic Psychiatry - Flammer, Erich; Frank, Udo; Steinert, Tilman (Frontiers in Psychiatry, 2020)
Background: In Germany, people suffering from severe mental illnesses who have committed severe offences and have considerably decreased or suspended criminal liability can be detained and treated in forensic psychiatric hospitals. In the German federal state Baden-Wuerttemberg all psychiatric hospitals including forensic psychiatric hospitals are obliged to record data on each coercive intervention and to submit them to a central registry. The objective of this study was to determine key measures for the use of seclusion and restraint and to compare them with data from the same registry of the general psychiatric hospitals. Methods:Data on main psychiatric diagnosis according to ICD-10, kind and duration of each coercive measure and occupancy according to diagnoses and cumulated number of days of treatment from all 8 forensic facilities in the state of Baden-Wuerttemberg covering a catchment area with about 11 million inhabitants was collected on treated-case-level for three years. Results: 22.6 % of the cases treated in 2017 in forensic psychiatric hospitals were subjected to seclusion, and 3.8 % were subjected to mechanical restraint. The mean cumulated duration of seclusion episodes per affected case was 343.9 hours and the mean cumulated duration of restraint episodes was 261.7 hours. 13.2 % of the treated cases were subjected to room confinement with a mean cumulated duration of 539.1 hours per affected case. Involuntary medication was applied in 1.9 % of the cases. In general psychiatry, 2.9 % of the treated cases were subjected to seclusion, and 4.7 % were subjected to mechanical restraint. The mean cumulated duration per affected case amounted to 32.2 hours for seclusion episodes and to 37.6 hours for restraint episodes. Involuntary medication was applied in 0.6 % of the cases. Conclusion: Compared to general psychiatry, mechanical restraint is used significantly less frequently and seclusion significantly more frequently than in general psychiatry. Room confinement is used only in forensic psychiatric hospitals. Use of involuntary medication is rare, reflecting the high legal threshold as well as the efforts to motivate voluntary acceptance. The long duration of freedom-restricting coercive measures in forensic psychiatry probably reflects the selection of patients at high risk of violence.